Le temps long du hirak : le passé et ses présences - Giulia Fabbiano (L’Année du Maghreb)
Seven months after the beginning of the Algerian popular uprising, even as its political solution remains uncertain, its inscription in the longue-durée of history has certainly been achieved. Astonishing in scale, duration, and national roots, in its pacifism and creativity, the hirak is renewing the relationship of a population with itself, its past, and its future. In other words, there is a refashioning of history and the emergence of a collective consciousness. In the short-term the event also embodies multiple ways of being in time. This article will analyze its logic and effects. In other words, it proposes to study the revolutionary movement as a place - a breach - to examine the actions, the arrangements, and the uses of the past. These heterogeneous and contemporary presences are analyzed in terms of transpositions, commemorations, and renewals.